Mapping review on the study of brand loyalty in the sports industry - Barbosa, Ruby Lorena Carrillo; Rincón, Alfredo Guzmán; Saavedra, Nestor Ordoñez (International Journal of Innovative Research and Scientific Studies, 2025)
Brand loyalty is not merely a buzzword in the sports industry; it is a crucial factor for the sustainability of sports organizations. Sports managers do not just create brands that stand out in the market; they craft experiences that resonate with consumers, fostering strong and lasting relationships. This study aims to synthesize accumulated evidence on brand loyalty in the sports industry, identifying trends and emerging research areas. A mapping review was conducted following five steps, identifying 195 relevant documents. The scientific output has shown a significant increase since 2010. Results highlight the need for a holistic approach and suggest exciting future research opportunities in underrepresented contexts and regions. Satisfaction, service quality, and robust digital strategies are crucial for fostering brand loyalty.